2011
DOI: 10.7150/ijbs.7.74
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2-induced cytokine production enhances endometrial carcinoma cell survival and migration

Abstract: Lipocalin-2 (Lcn-2) is an acute-phase protein that has been implicated in diverse physiological processes in mice, including: apoptosis, ion transport, inflammation, cell survival, and tumorigenesis. This study characterized the biological activity of Lcn-2 in human endometrial carcinoma cells (RL95-2). Exposure of RL95-2 cells to Lcn-2 for >24 h reduced Lcn-2-induced cell apoptosis, changed the cell proliferation and up-regulated cytokine secretions, including: interleukin-8 (IL-8), inteleukin-6 (IL-6), monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…The finding supports a relationship between LCN2 and angiogenesis during the growth of endometrial tissue within the peritoneum. We have previously shown that LCN2 stimulates the secretion of angiogenesis-related cytokines from an endometrial cell line (RL95-2; Lin et al 2011). Our current study showed time-dependent production of LCN2, which supports the idea that LCN2 stimulates the expansion of ectopic endometrial tissue in the peritoneum.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The finding supports a relationship between LCN2 and angiogenesis during the growth of endometrial tissue within the peritoneum. We have previously shown that LCN2 stimulates the secretion of angiogenesis-related cytokines from an endometrial cell line (RL95-2; Lin et al 2011). Our current study showed time-dependent production of LCN2, which supports the idea that LCN2 stimulates the expansion of ectopic endometrial tissue in the peritoneum.…”
Section: Discussionsupporting
confidence: 78%
“…As mentioned earlier, LCN2 is upregulated in the endometriotic lesions (Konno et al 2007, Becker et al 2010. We previously found that LCN2 is upregulated in the endometrial carcinoma cells (RL95-2 cells derived from endometrial epithelia) under oxidative stress and that LCN2-induced secreted cytokines trigger cell proliferation and migration (Lin et al 2011). These findings indicate that LCN2 is a stress factor that responds to environmental stress by triggering changes in cellular physiology.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Lin and colleagues reported that LCN2 treatment induced cell apoptosis up to 48 hours in endometrial carcinoma RL95-2 cells. However, LCN2 simultaneously induced IL-8 expression which enhanced cell survival and migration after 48 hours (Lin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 thereby offers the potential to promote the formation of tumor (48). Based on the result of Lin et al (41), LCN2 could induce IL-8 expression and secretion and enhance cell migration and invasion. This suggests IL-8 as an LCN2-induced tumor factor.…”
Section: Acute-phase Proteins Related To Cytokinesmentioning
confidence: 99%